Molecular Mechanisms of Gonadotropin-Inhibitory Hormone (GnIH) Actions in Target Cells and Regulation of GnIH Expression - Son, You Lee; Ubuka, Takayoshi; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2019)
Since gonadotropin-inhibitory hormone (GnIH) was discovered in 2000 as the first hypothalamic neuropeptide that actively inhibits gonadotropin release, researches conducted for the last 18 years have demonstrated that GnIH acts as a pronounced negative regulator of reproduction. Inhibitory effect of GnIH on reproduction is mainly accomplished at hypothalamic-pituitary levels; gonadotropin-releasing hormone (GnRH) neurons and gonadotropes are major targets of GnIH action based on the morphological interaction with GnIH neuronal fibers and the distribution of GnIH receptor. Here, we review molecular studies mainly focusing on the signal transduction pathway of GnIH in target cells, GnRH neurons and gonadotropes. The use of well-defined cellular model systems allows the mechanistic study of signaling pathway occurring in target cells by demonstrating the direct cause-and-effect relationship. The insights gained through studying molecular mechanism of GnIH action contribute to deeper understanding of the mechanism of how GnIH communicates with other neuronal signaling systems to control our reproductive function. Reproductive axis closely interacts with other endocrine systems, thus GnIH expression levels would be changed by adrenal and thyroid status. We also briefly review molecular studies investigating the regulatory mechanisms of GnIH expression to understand the role of GnIH as a mediator between adrenal, thyroid and gonadal axes.